2022
DOI: 10.4317/jced.59975
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthodontic forces on calcitonin gene-related peptide (CGRP) expression in the human periodontal ligament and its relationship with the human dental pulp

Abstract: Background The purpose of this study was to quantify the effect of moderate and severe orthodontic forces on Calcitonin gene-related peptide (CGRP) expression in the healthy human periodontal ligament (PDL) and its possible relationship with the human dental pulp. Material and Methods Ninety human periodontal ligament samples were obtained from healthy premolars where extraction was indicated for orthodontic reasons. Prior to extraction, teeth were divided in 3 groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Orthodontic forces were found to be associated with increased flow of blood, reduction in pulpal volume, more inflammation, and CGRP expression. However, no increase in caries or root canal treatment incidence was reported during orthodontic treatment [11][12][13][14][15]. Hatrom et al studied the changes in pulp volume and root length of the upper anteriors requiring en masse retraction with and without piezo-orthodontics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthodontic forces were found to be associated with increased flow of blood, reduction in pulpal volume, more inflammation, and CGRP expression. However, no increase in caries or root canal treatment incidence was reported during orthodontic treatment [11][12][13][14][15]. Hatrom et al studied the changes in pulp volume and root length of the upper anteriors requiring en masse retraction with and without piezo-orthodontics.…”
Section: Resultsmentioning
confidence: 99%
“…Caviedes-Bucheli et al assessed the CGRP levels after subjecting premolars that were planned for extraction to different intensities of orthodontic forces. They observed that levels of CGRP were proportional to the amount of force applied; the teeth subjected to greater force showed greater expression of CGRP by radioimmunoassay [ 12 ]. Mago et al evaluated the effect of orthodontic forces applied to upper premolars [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…In line with previous studies, some CGRP‐labeled fibers appeared to have no obvious relation to blood vessels and terminated as free fiber endings in the surrounding periodontal tissue (Byers, 1985 ; Heyeraas et al., 1993 ; Luthman et al., 1992 ; Uddman et al., 1984 ; Wakisaka et al., 1987 ). CGRP released from peptidergic C‐fibers in response to mechanical stress is immediate, increases the sensitivity of nociceptors by triggering the release of inflammatory mediators, and may lead to root resorption if the stress is sustained (Caviedes‐Bucheli et al., 2022 , 2008 ; Vandevska‐Radunovic, 1999 ). In the present study, we also found that the CGRP‐labeled free endings that innervated the periodontal ligament were organized in a “basket”‐like manner around the roots of the molar.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies have reported OTM resulted in increased release and concentrations of pulpal angiogenic growth factors that enhanced angiogenesis 29–32 . Furthermore, the finding of increased calcitonin gene‐related peptide (CGRP) expression in the human periodontal ligament (PDL) of teeth subjected to orthodontic forces, may affect the way the dental pulp responds to different stimuli 33 . The CGRP released from C‐fibres with OTM regulates inflammation by controlling vascular tone and blood flow, which results in the dynamic changes to the microcirculation in the PDL and pulp 34 .…”
Section: Orthodontics and The Pulpmentioning
confidence: 99%
“…[29][30][31][32] Furthermore, the finding of increased calcitonin gene-related peptide (CGRP) expression in the human periodontal ligament (PDL) of teeth subjected to orthodontic forces, may affect the way the dental pulp responds to different stimuli. 33 The CGRP released from C-fibres with OTM regulates inflammation by controlling vascular tone and blood flow, which results in the dynamic changes to the microcirculation in the PDL and pulp. 34 Such microcirculatory disturbances in the pulp can affect pulp metabolic activity, 35 subsequently impacting pulp sensibility such that electric pulp testing (EPT) is unreliable due to an increase in the response threshold, albeit reversible over time.…”
Section: Physiological Effectsmentioning
confidence: 99%